INTRODUCTION AND EDUCATION OF SORTING ORGANIC AND NON-ORGANIC WASTE IN STUDENTS AT SDN 03 RANTAU SELATAN - Simbolon, Pratiwy Br.; Prayoga, Yudi; Herawati Limbong, Christine (Abdi Dosen : Jurnal Pengabdian Pada Masyarakat, 2023)
Garbage is part of human life. Garbage is left over objects that are not used. Garbage should receive serious attention and handling. Due to the lack of understanding of the community and the government, as well as the lack of funds and income for the majority of the community, the waste problem is often neglected. Currently, most people are aware of the effects of waste, which include causing adverse flooding, disease and odors that can interfere with life, but this is not balanced by the behavior of the people themselves. Changes in behavior can be done through habits that have been practiced since school age. Learning for school-age children is an important stage for habituation of behavior. This community service activity aims to increase public knowledge about waste starting at school age. This goal is realized by providing information about waste to SD 03 Rantau Selatan students. The methods used in this activity are presentations, demonstrations and practice of sorting waste. It is hoped that through this activity the children of SD 03 Rantau Selatan will be able to recognize, differentiate and practice waste sorting. The results of this activity were able to increase children's knowledge and habits in disposing of garbage in its place.